2022
DOI: 10.6007/ijarped/v11-i4/16076
|View full text |Cite
|
Sign up to set email alerts
|

Learning through Play in Early Childhood: A Systematic Review

Abstract: Playing is the leading activity in kindergarten education, a unique form of activity that conforms to the age characteristics of preschool children, and an important way to promote the overall and healthy development of children's bodies and minds. This research's purpose was to carry out a literature systematic review on the learning through play in early childhood. This review was estimated on the steps pointed in the PRISMA criteria, as well as new research that merged different research designs. The public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
1
1
Order By: Relevance
“…In addition, corresponding to Vogt et al (2018) findings on parents preferring the traditional methods of teaching, this study also reported that very little was made known to them about play as a method of teaching in comparison to the amount of information given either in weekly comments or during Report Card sessions about the schools' efforts to enhance their children's success through the traditional ways of teaching and learning that included reading, writing and arithmetic. However, interestingly, some of the findings reported by this study on parents' preferences of the traditional teaching methods shows contradicting viewpoints from the findings of a systematic review conducted by (Yee et al, 2022). The review which discusses how parents viewed PBL, points out that the roles and functions of parents and teachers were found to be significant in supporting the implementation of play-based learning in preschool settings.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In addition, corresponding to Vogt et al (2018) findings on parents preferring the traditional methods of teaching, this study also reported that very little was made known to them about play as a method of teaching in comparison to the amount of information given either in weekly comments or during Report Card sessions about the schools' efforts to enhance their children's success through the traditional ways of teaching and learning that included reading, writing and arithmetic. However, interestingly, some of the findings reported by this study on parents' preferences of the traditional teaching methods shows contradicting viewpoints from the findings of a systematic review conducted by (Yee et al, 2022). The review which discusses how parents viewed PBL, points out that the roles and functions of parents and teachers were found to be significant in supporting the implementation of play-based learning in preschool settings.…”
Section: Discussioncontrasting
confidence: 72%
“…Nonetheless, although parents do finally understand that play-based learning is important for the child's development, a major concern in the context of Malaysia among parents has and will always be about play-based learning and its impact on children's academic success. Despite the systematic review by Yee et al (2022) and various other international statements including that from NAEYC, UNESCO and UNICEF that posits the benefits of play based learning (PBL) on a child's growth and development, this study fund a deep gap in the implementation of PBL in the ECE context in Malaysia. The result of this study is parallel to that of Tee and Mariani (2018) indicating PBL implementation in the Malaysian preschool education scenario to be far behind as majority child-centred learning where children participate actively in their own process of learning is not being practised in most Malaysian preschool settings.…”
Section: Discussionmentioning
confidence: 85%